Manipulative bulletin board for early categorization - Skoumpourdi, Chrysanthi (Teaching Mathematics and Computer Science, 2011)
According to various researchers categorization is a developmentally appropriate mathematical concept for young children. Classifying objects also relates to every day activities of human life. The manipulative bulletin board (MBB) served as a kind of auxiliary means for approaching categorization by young children. In this article we investigated the kind of MBB that pre-service early childhood education teachers constructed in order to involve children in tasks of categorization, as well as, the way children manipulated these boards in order to categorize items. The MBB, as teaching aids, facilitated the engagement of the children in different categorization processes.